EDUCATION AND BUSINESS PARTNERSHIP: IN SEARCH OF NEW FORMS OF INTERACTION - Khoruzha, Liudmyla; Tadeush, Olena (Continuing Professional Education: Theory and Practice, 2020)
The article analyzes modern approaches to the partnership interaction between education and business, characterizes the specific features and modern forms of partnership interaction between higher educational institutions and business corporations. The authors have established that the partnership between higher education and business is a very specific type of cooperation and involves a wide range of activities, multifaceted goals and multifunctional opportunities. The researchers emphasize that establishing a productive mechanism for cooperation between universities and business will increase the efficiency of educational activities and develop ways of technology transfer to production, because this partnership is mutually beneficial, since the university receives additional financial resources and practical focus of its activities and the company gets qualified professionals and advanced technologies. The authors have described the Master’s Educational and Professional Program «Corporate Education and Staff Development» in Specialty 011 «Educational, Pedagogical Sciences». The purpose of the educational program is to provide theoretical and practical training for the specialists capable of creating and operating alternative education systems in corporations and enterprises that provide training, advanced studies and continuous development of the staff in accordance with the strategic goals and objectives of these institutions. The authors have presented the content of the educational program, competencies and program outputs, a selective block of educational disciplines and prospects for employment of graduates.